2011
DOI: 10.1007/s11999-011-1883-1
|View full text |Cite
|
Sign up to set email alerts
|

Sterility of the Personal Protection System in Total Joint Arthroplasty

Abstract: Background Bacteria shed by operating room personnel is a source of wound contamination and postoperative infections. The personal protection system (PPS) was designed to decrease airborne bacteria and intraoperative contamination in total joint arthroplasty. Questions/purposes We determined the microbial contamination rate of the PPS and incidence of contamination with key pathogens, Staphylococcus aureus and coagulasenegative staphylococci. Patients and Methods We prospectively evaluated PPS contamination in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 18 publications
0
13
0
3
Order By: Relevance
“…They demonstrated a contamination rate as high as 80% with Staphylococcus aureus being the most prevalent organism cultured [16]. A similar study by Kearns et al [17] showed contamination of the surgical hood in 48 of 102 (47%) of cases. Perhaps most comparable with our study was a recent investigation by Young et al, in which a similar mock surgical gowning procedure was performed with fluorescent powder on the surgeon’s hands to simulate normal squamous cells.…”
Section: Discussionmentioning
confidence: 93%
“…They demonstrated a contamination rate as high as 80% with Staphylococcus aureus being the most prevalent organism cultured [16]. A similar study by Kearns et al [17] showed contamination of the surgical hood in 48 of 102 (47%) of cases. Perhaps most comparable with our study was a recent investigation by Young et al, in which a similar mock surgical gowning procedure was performed with fluorescent powder on the surgeon’s hands to simulate normal squamous cells.…”
Section: Discussionmentioning
confidence: 93%
“…Kearns et al demonstrated that the external surface of the PPS cannot be assumed to be sterile after removal from the original packaging, and they suggested the need to change gloves if the PPS is touched or adjusted during the procedure. 46 Other authors agree with the consideration of PPS as more a personal ‘protection’ than equipment specifically to reduce PJI. 7,8,39 …”
Section: Intra-operative Factorsmentioning
confidence: 97%
“…szczepami bakterii z rodzaju Bacillus, Micrococcus czy Staphylococcus. Ten rodzaj kontaminacji należy uwzględnić przy doborze rękawiczek przeznaczonych do stosowania podczas wykonywania procedur u pacjentów z upośledzonym układem odporności [4].…”
Section: Historia Rękawicunclassified